Effect of diuretics on plasma aldosterone and potassium in primary hypertension: A systematic review and meta‐analysis - McNally, Ryan J.; Farukh, Bushra; Chowienczyk, Philip J.; Faconti, Luca (British journal of clinical pharmacology, 2022)
Aim By contrast with drugs inhibiting the renin‐angiotensin‐aldosterone system (RAAS), diuretics stimulate renin release by the kidneys. Although plasma aldosterone (PA) is thought to be mainly regulated by RAAS activity, serum potassium has been shown to be an important factor in animal models and humans. Here we perform a systematic review and meta‐analysis of randomised controlled trials (RCT) in hypertension investigating the effects of diuretic therapy on PA and the correlation of change in PA with that of potassium and blood pressure (BP). Methods Three databases were searched: MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials (CENTRAL). Titles were first screened by title and for relevance before full‐text articles were assessed for eligibility according to a predefined inclusion/exclusion criteria. Results A total of 1139 articles were retrieved, of which 42 met the prespecified inclusion/exclusion criteria. The average standardised difference in mean PA was similar for all classes of diuretic: thiazide/thiazide‐like 0.299 (95% confidence interval [CI] 0.150, 0.447), loop 0.927 (0.37, 1.49), MRA/potassium‐sparing 0.265 (0.173, 0.357) and combination 0.466 (0.137, 0.796), Q = 6.33, P = .097. In subjects untreated with another antihypertensive, there was a significant relationship between change in PA and change in systolic BP but no relationship with the change in potassium. Conclusion In RCTs of diuretic therapy in hypertension, there is an increase in PA with all classes of diuretic and no significant between‐class heterogeneity. Change in PA is not related with potassium but correlates with the change in BP in subjects untreated with another antihypertensive medication.